2012
DOI: 10.1038/jp.2012.84
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sildenafil on retinopathy of prematurity in very preterm infants

Abstract: Sildenafil treatment did not affect ROP progression or increase the need for laser treatment in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
(29 reference statements)
0
18
0
3
Order By: Relevance
“…52,53 Whereas case reports have linked sildenafil treatment with potentially enhanced ROP progression and severity, 53 subsequent retrospective crosssectional studies have found no adverse outcomes in premature infants with ROP who were treated with sildenafil for pulmonary hypertension. 54,55 Previous studies of the effects of PDE5 inhibitors in the eye have focused largely on retinal and choroidal blood flow, showing increased choroidal congestion and ophthalmic artery velocity and flow, with controversial results in the retinal vasculature. 56,57 Using ex vivo human retinal tissue to study the distribution of PDE5, researchers have shown that in addition to retinal and choroidal vasculature, PDE5 was expressed in retinal ganglion and bipolar cells.…”
Section: Existing Data For Retinal Side Effects Of Sildenafil In Humamentioning
confidence: 99%
“…52,53 Whereas case reports have linked sildenafil treatment with potentially enhanced ROP progression and severity, 53 subsequent retrospective crosssectional studies have found no adverse outcomes in premature infants with ROP who were treated with sildenafil for pulmonary hypertension. 54,55 Previous studies of the effects of PDE5 inhibitors in the eye have focused largely on retinal and choroidal blood flow, showing increased choroidal congestion and ophthalmic artery velocity and flow, with controversial results in the retinal vasculature. 56,57 Using ex vivo human retinal tissue to study the distribution of PDE5, researchers have shown that in addition to retinal and choroidal vasculature, PDE5 was expressed in retinal ganglion and bipolar cells.…”
Section: Existing Data For Retinal Side Effects Of Sildenafil In Humamentioning
confidence: 99%
“…It is also an attractive therapeutic option for infants with pulmonary hypertension caused by BPD because it can be given orally, and over longer periods of time with apparent low toxicity. Several case series of infants with pulmonary hypertension and BPD have shown short-term improvements in pulmonary hemodynamics and gas exchange in those treated with oral sildenafil 78, 79 . These early studies suggest that sildenafil is well tolerated in infants with pulmonary hypertension and BPD and leads the way to future RCTs evaluating sildenafil in pulmonary hypertension associated with BPD.…”
Section: Introductionmentioning
confidence: 99%
“…No abnormal auditory or ophthalmologic exams were noted at the time of discharge. Steiner et al (2014) 36 AE with sildenafi l: pulmonary hemorrhage (2/6 patients, at a time point when signifi cant improvement of PH had already taken place; both survived) Fang et al (2013) 39 AE: Stage 3 ROP, 4 (23.5%) in sildenafi l group, 6 (11.8%) in controls; progression of ROP, 5(29%) in sildenafi l group, 12 (24%) in controls; OR (sildenafi l) = 1.35, 95% CI, 0.39-4.62; P = .63. SAE: 1 infant in each group required laser treatment.…”
Section: Are Pde5 Inhibitors Effective In Improving Clinical Outcomesmentioning
confidence: 99%
“…41,42 One study that reviewed the ophthalmologic adverse effects of sildenafil in very premature infants reported that treatment did not affect retinopathy of prematurity (ROP) progression or need for laser treatment (P = .63) ( Table 4, Supplemental Table 20). 39 The evidence is insufficient to allow definitive statements about the toxicities of sildenafil due to the small number of studies with inconsistent results.…”
Section: What Toxicities Are Associated With Use Of Pde5 Inhibitors Imentioning
confidence: 99%